Implementación de un prototipo de robot antropomórfico para la introducción a la industria 4.0, mediante un entorno 3d de realidad virtual - Casa Chango, Cristian Alexander (2022)
Actually, most industrial processes are developed with conventional technology. Therefore, the 4.0 industry and intelligent manufacturing beginning provides technological applications such as physical Cyber Systems, whose allow the physical medium fusion with the virtual one, by giving a 16.1% low percentage, due to the knowledge lack, which still exists around the fourth revolution industrial. This project is based onto a design process, by using virtual reality as a complementary tool. This a didactic module consists into an industrial anthropomorphic robot system developed, through a physical prototype that simulates repetitive processes for user training around real work, the same one that is made, through CAD modeling and 3D printing based on filament (PLA) , the design of the virtual application is executed, by Unity 3D, whose allows an industrial environment simulation, being the environment friendly for interaction and immersion with user, it is important to indicate, which the module is based onto an immersion degree that is the system not immersive. This system is validated with a serial communication, whose allows the virtual application and the physical prototype to interact, simultaneously, further it, it is got the anthropomorphic robot freedom degrees, which are captured onto LCD screen, by means the I2C protocol, being a complementary module at a technological level into robotics area.